2000
DOI: 10.1002/1098-2329(200023)19:3<180::aid-adv3>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of polypropylene–polystyrene blends: Part 2, crystallization behavior and mechanical properties

Abstract: Reactor produced blends of polypropylene (PP) and polystyrene (PS) are obtained by graft copolymerization of styrene onto polypropylene chains. This technique generates simultaneously a graft copolymer (PP-g-PS) and polystyrene homopolymer. The resulting blends, however, have a low impact resistance and have to be modified with the addition of rubbery toughening agents, such as an ethylene propylene copolymer (EPR) or a styrene-b-ethylene-alt-butylene-b-styrene (SEBS) triblock copolymer, in a downstream compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Usually, such compatibilizers have blocks or graft segments that are chemically identical to those in the respective phases and work by improving the interfacial adhesion . Poly (styrene‐ b ‐butadiene‐ b ‐styrene) (SBS), poly(styrene‐ b ‐ethylene‐ co ‐butylene‐ b ‐styrene) (SEBS), poly(styrene‐ b ‐ethylene‐ co ‐propylene) (SEP), poly(styrene‐ b ‐isoprene‐ b ‐styrene) (SIS), and PP‐ g ‐PS copolymers can be used as compatibilizing agents for PP/PS blends. Among which, PP‐ g ‐PS graft copolymer, composed of a PP backbone and PS branches, is an ideal compatibilizer for PP/PS blends due to the good compatibilities of PP backbone and PS branches with PP bulk and PS bulk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, such compatibilizers have blocks or graft segments that are chemically identical to those in the respective phases and work by improving the interfacial adhesion . Poly (styrene‐ b ‐butadiene‐ b ‐styrene) (SBS), poly(styrene‐ b ‐ethylene‐ co ‐butylene‐ b ‐styrene) (SEBS), poly(styrene‐ b ‐ethylene‐ co ‐propylene) (SEP), poly(styrene‐ b ‐isoprene‐ b ‐styrene) (SIS), and PP‐ g ‐PS copolymers can be used as compatibilizing agents for PP/PS blends. Among which, PP‐ g ‐PS graft copolymer, composed of a PP backbone and PS branches, is an ideal compatibilizer for PP/PS blends due to the good compatibilities of PP backbone and PS branches with PP bulk and PS bulk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the few cases for which the physical origin of the increased T c was discussed, the nucleation effect was attributed to the increased surface area of the dispersed phase after dynamic vulcanization and/or (reactive) compatibilization. 7,8,13 This paper discusses the influence of graft copolymer formation on dispersed rubber particles on the crystallization kinetics and crystalline morphology of the semi-crystalline matrix. A low-molar-mass poly(ethylene oxide) dimethacrylate (PEO9) resin is used as the rubber precursor, which is fully miscible with PCL above its melting temperature.…”
mentioning
confidence: 99%
“…15,16 Similar changes in the crystallization behavior were observed after compatibilization of polymer blends by the addition of copolymers in the absence of crosslinking. Tang and Huang 12 reported an increase in T c for blends of PP and poly(ethylene oxide) (PEO) by compatibilization with a maleated PP-PEO copolymer, whereas Adewole et al 13 observed an increase in T c for PP in blends with poly (styrene) (PS) after the addition of a PP-PS graft copolymer. In the few cases for which the physical origin of the increased T c was discussed, the nucleation effect was attributed to the increased surface area of the dispersed phase after dynamic vulcanization and/or (reactive) compatibilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their blends usually result in serious phase separation, low interfacial adhesion, and poor mechanical properties. As a compatibilizer, the PP‐ g ‐PS copolymer actually improves the interfacial adhesion and produces a finer dispersion mixing of PP/PP‐ g ‐PS/PS polymer blends and, thus, enhances the mechanical properties 4–11. Researchers have reported the development of morphologies and the rheological and isothermal crystallization behaviors of PP/PP‐ g ‐PS/PS polymer blends in detail.…”
Section: Introductionmentioning
confidence: 99%